PROBLEMS AND DEVELOPMENT PROSPECTS OF INCLUSIVE EDUCATION IN UZBEKISTAN - Pirniyazova, Gulchira Nietbaevna (SCIENCE and SOCIETY, 2026)
In this article, we analyzed the current state of the inclusive education system in Uzbekistan, its current problems and prospects for its development. Inclusive education is one of the important social processes aimed at creating equal educational opportunities for all members of society, including children with disabilities. In the article, we highlighted the main problems encountered in the process of introducing inclusive education in our country, as well as issues such as insufficient training of pedagogical personnel, lack of special educational and methodological materials, and insufficient adaptation of the material and technical base of educational institutions. We also considered that the attitude of parents and society to inclusive education is also an important factor. During the study, we substantiated the need to introduce modern pedagogical technologies, train qualified specialists, provide educational institutions with appropriate infrastructure, and effectively use international experience to develop inclusive education. At the end of the article, proposals and recommendations are made for the development of an inclusive education system in Uzbekistan, emphasizing that improving this system is of great importance in ensuring social equality in society, as well as in realizing the right of every child to education.
Keywords: inclusive education; children with special needs; equal opportunities; pedagogical approach; social integration; educational policy; pedagogical personnel; innovative methods; educational system.